FAKTOR-FAKTOR YANG MEMENGARUHI FIRM VALUE PADA PERUSAHAAN NON-KEUANGAN - Felicia Puspita; Jenny Vivianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to determine the effect of firm size, profitability, leverage, liquidity, activity ratio, managerial ownership and institusional ownership on firm value. The object of this research is non-financial companies listed on the Indonesia Stock Exchange consistently from 2018 until 2020. This research uses a purposive sampling method for selecting the sample, there are 100 non-financial companies listed on the Indonesia Stock Exchange which are the samples of this research. In this research the data is researched by multiple linear regression. The results of the study indicate that profitability, leverage and activity ratio have an influence on firm value. But, firm size, liquidity, managerial ownership and institusional ownership do not have an influence on firm value.